Development of Android-Assisted Sound Wave Experiment Devices as an Effort to Improve High School Students' Motivation and Physics Learning Outcomes - Edwana, Neiny; Islami, Nur; Zulirfan, Zulirfan (Journal of Educational Sciences, 2023)
The experimental device of sound wave in high school rarely available. This study conducted to develop a android-assisted sound wave experiment device. The experiment consist of four type of activities such as linear and circular motion effect dopler, interference and resonance. The study utilized the developmental research design by applying the ADDIE Model. The developed experiment device validity obtained from the expert while its practicality conducted by students and physics teacher consist of 10 students and 2 physics teacher. Based on the results of the effectiveness test on students stated that the android-assisted sound wave experimental device was declared effective in increasing motivation and learning outcomes. With an average evaluation of the motivation of the experimental class 85.56 higher than the control class with an average of 76. The average evaluation of the learning outcomes of the experimental class is 85.07 higher than the control class with a value of 75.22. Thus the developed android-assisted sound wave experimental device has been declared valid, practical and effective for use as a learning medium in teaching and learning activities in the classroom to increase learning motivation and student learning outcomes.